Reflective ESP Practice: Teachers' Beliefs, Methods, and Negotiating Institutional Realities - Salsabila Ramadhani Imanda; Niamika El Khoiri; Sari Karmina (Didaktika: Jurnal Kependidikan, 2025)
This single-case study explores the belief-practice dynamics of Pippa, an experienced English for Specific Purposes (ESP) teacher in an Economics Development program, utilizing a reflective practice approach. The study investigated the extent to which her pedagogical beliefs align with her classroom practices, and how institutional realities mediate this relationship. Data were triangulated through a pre-observation interview, classroom observation of an academic writing session (biography writing), and a critical post-observation interview. Thematic analysis of the data revealed a complex interplay characterized by conditional alignment and institutional mediation. While Pippa professed a belief in consistently correcting errors and promoting the use of English, her practice demonstrated strategic adaptation: L1 (Indonesian) use was tolerated to maintain student confidence, and pronunciation correction was applied selectively based on task demands (e.g., minimal correction during reading aloud versus stricter application during speaking tasks). Crucially, divergence was found to be largely driven by external constraints that emerged from the data, including the student level mismatch (low-beginner students in an ESP course) and the institutional culture emphasizing "fun but not strict.". These pressures compelled Pippa to assume the role of an adaptive mediator, resulting in a pragmatic redefinition of success (i.e., prioritizing that students "at least learn something" over achieving ideal ESP objectives). This study contributes to the literature by highlighting the conditional and evolutionary nature of experienced teachers’ beliefs, underscoring that belief realization is a constant negotiation between cognitive ideals and the empirical realities of the institutional context.